Pengaruh Literasi Pajak dan Kualitas Pelayanan Digital terhadap Kepatuhan Wajib Pajak PPh di Era Transformasi Digital pada UMKM di Kota Makassar - Putri Nandini; Samirah Dunakhir; Nur Afiah (UNIVERSITAS DHARMAWANGSA, 2026)
Tax compliance remains one of the major challenges in Indonesia's taxation system, particularly among Micro, Small, and Medium Enterprises (MSMEs). The implementation of digital tax services through DJP Online and Coretax Administration System is expected to improve taxpayer compliance in the era of digital transformation. This study aims to examine the effect of tax literacy and digital service quality on income taxpayer compliance among MSMEs in Makassar City. The research employed a quantitative approach using a survey method. Data were collected through questionnaires distributed to MSME taxpayers and analyzed using multiple linear regression with SPSS. The findings indicate that tax literacy has a positive and significant effect on taxpayer compliance. Likewise, digital service quality positively and significantly affects taxpayer compliance. Simultaneously, tax literacy and digital service quality significantly influence taxpayer compliance. These findings imply that improving taxpayer knowledge and enhancing the quality of digital tax services are essential strategies to increase MSME tax compliance in the digital transformation era.